Ability of minimally invasive surgery to decrease incisional surgical site infection occurrence in patients with colorectal cancer and other gastroenterological malignancies - Yamamoto, Takehito; Yoshitomi, Mami; Oshimo, Yoshiki; Nishikawa, Yuta; Hisano, Koji; Nakano, Kenzo; Kawai, Takayuki; Okuchi, Yoshihisa; Iguchi, Kohta; Tanaka, Eiji; Fukuda, Meiki; Taura, Kojiro; et al. (Frontiers in Surgery, 2023)
Background: Surgical site infection (SSI) is one of the most important complications of surgery for gastroenterological malignancies because it leads to a prolonged postoperative hospital stay and increased inpatient costs. Furthermore, SSI can delay the initiation of postoperative treatments, including adjuvant chemotherapy, negatively affecting patient prognosis. Identifying the risk factors for SSI is important to improving intra- and postoperative wound management for at-risk patients. Methods: Patients with gastroenterological malignancies who underwent surgery at our institution were retrospectively reviewed and categorized according to the presence or absence of incisional SSI. Clinicopathological characteristics such as age, sex, body mass index, malignancy location, postoperative blood examination results, operation time, and blood loss volume were compared between groups. The same analysis was repeated of only patients with colorectal malignancies. Results: A total of 528 patients (330 men, 198 women; mean age, 68±11 years at surgery) were enrolled. The number of patients with diseases of the esophagus, stomach, small intestine, colon and rectum, liver, gallbladder, and pancreas were 25, 150, seven, 255, 51, five, and 35, respectively. Open surgery was performed in 303 patients versus laparoscopic surgery in 225 patients. An incisional SSI occurred in 46 patients (8.7%). Multivariate logistic regression analysis showed that postoperative hyperglycemia (serum glucose level ≥140 mg/dL within 24 hours after surgery), colorectal malignancy, and open surgery were independent risk factors for incisional SSI. In a subgroup analysis of patients with colorectal malignancy, incisional SSI occurred in 27 (11%) patients. Open surgery was significantly correlated with the occurrence of incisional SSI (P=0.024). Conclusions: Postoperative hyperglycemia and open surgery were significant risk factors for SSI in patients with gastroenterological malignancies. Minimally invasive surgery could reduce the occurrence of incisional SSI, especially in patients with colorectal malignancies.